Save It For a Rainy Day! Lean Strategies for Cost Saving: The Role of Lean Maturity - Norhana, Mohd Aripin; Nawanir, Gusman; Suhaidah, Hussain (OmniaScience, 2023)
Purpose: This study investigates the effect of lean implementation on production cost reduction and the moderating role of lean manufacturing maturity. Design/methodology/approach: This study employed a cross-sectional survey, of which the samples were drawn using a cluster sampling procedure from 151 middle and top-level management of medium and large manufacturing companies gathered from the Federation of Manufacturers Malaysia (FMM). Data were analyzed using the PLS-SEM approach through SmartPLS4 software. Findings: The result revealed that lean implementation does not leverage production cost reduction as the lean journey requires long-term orientation, which finally leads to valid cost reduction. The moderating role of lean manufacturing maturity was significant and positive in the relationship between lean manufacturing implementation and production cost reduction. Research limitations/implications: Future research should include longitudinal settings as this study is cross-sectional, and future research might put the present model to the test in multiple industries and regions, including a cross-country comparison to improve the generalizability of the findings. Additionally, further studies could extend this study using a mixed-method approach. Practical implications: By offering a holistic perspective, this study expands the existing literature, contributes to knowledge of integrated lean implementation and supports the management in planning their path towards cost-cutting performance. Originality/value: This study answers the inconclusive finding between lean implementation and operational performance in terms of production cost reduction. The study contributes to the body of knowledge and, most importantly, to the practitioners in planning their lean journey.